Disease Extermination - A Digital Educational Game on Vaccines, Viruses and Bacteria - Ramos, Gustavo; Lessa, Laura; Cavalcanti, Diana Cabral (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2017: Proceedings of the 23rd Brazilian Symposium on Multimedia and the Web, 2017)
The educational game Disease Extermination presents how the vaccines act in the organism and how they prevent viruses and bacteria from parasite in the human organism. The game is based on mechanical shooter game, whose game simulates as a scenario the human body internally and the player uses strategics to protect the organism against invaders represented by viruses or bacterias. The game has the role of raising awareness about the importance of Vaccination. Usually many users do not adopt the vaccine, and so, diseases are not prevented.